Regimes of Meaning and Interaction in O Casarão da Rua do Rosário, by Menalton Braff - Ribeiro Santos, Flavia Karla; Duarte, Renata Cristina (Lingüística y Literatura, 2021)
We examine how conservative and progressive values emerge in Menalton Braff’s O Casarão da Rua do Rosário as the characters interact with each other and with the world built by literary language ,using the theoretical methodological reference of French semiotics ,. We focus on the feelings resulted from the oppression of a conservative matriarch with rigid moral and religious values and by the political regime in force in Brazil from 1964 until 1985. The analysis reveals the conflictive interaction between the matriarch and her younger sister, who, together with her children, rejects the conservative figured by the house they live.